2018
DOI: 10.22268/ajpp-036.1.075079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Plant Diseases and IPM Strategies

Abstract: There has been a remarkable scientific output on the topic of how climate change is likely to affect plant diseases. Climate change influences the occurrence, prevalence, and severity of plant diseases. Projected atmospheric and climate change will thus affect the interaction between crops and pathogens in multiple ways. This will also affect disease management with regard to timing, preference, and efficacy of chemical, physical, and biological measures of control and their utilization within integrated pest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 1 publication
0
18
0
1
Order By: Relevance
“…For example, impacts on pollinators (Kehrberger & Holzschuh, 2019), such as bees, are already under great pressure from habitat loss and intensive agriculture. The same is about the effects of global warming on pests and diseases in crops (Zayan, 2019) or livestock (Kebede et al, 2018).…”
Section: Introduction To the Sensitivity Of Food To Climatementioning
confidence: 99%
“…For example, impacts on pollinators (Kehrberger & Holzschuh, 2019), such as bees, are already under great pressure from habitat loss and intensive agriculture. The same is about the effects of global warming on pests and diseases in crops (Zayan, 2019) or livestock (Kebede et al, 2018).…”
Section: Introduction To the Sensitivity Of Food To Climatementioning
confidence: 99%
“…The impact of climate change on increases in plant pests is also of global concern because a lot of resources are required to control this problem. Zayan [ 76 ] indicated that in the US alone, farmers spent more than USD 11 billion for pest control. Additionally, they reported that global climate change could cause some plant pests to undergo from one to five additional lifecycles per season, increasing their ability to overcome plant pest resistance.…”
Section: Climate Change Effects On Plant Pathogens and Diseasesmentioning
confidence: 99%
“…After the introduction of the green revolution in Indonesia, rice pests and diseases outbreak became more frequent. In addition, changes in climatic factors such as temperature, rainfall and humidity highly affect crop production and insect population as well as pest-disease infestation [5].…”
Section: Introductionmentioning
confidence: 99%